A Study on the psychometric properties of the Chinese version of the Parent Tic Questionnaire - Qiang Ding; Douglas W. Woods; Kathryn E. Barber; Wen Xu; Ying Zhao; Shuqin Shen; Jinhua Sun (PLoS ONE, 2025)
Introduction The Parent Tic Questionnaire (PTQ) is a tool for parents to assess their child’s tic severity, but its effectiveness in non-Western contexts like China has not been thoroughly examined. This study aimed to evaluate the psychometric properties of the PTQ in assessing motor and vocal tic severity among Chinese children diagnosed with tic disorders. Method Parents of 268 Chinese children and adolescents aged 6–17 years, diagnosed with tic disorders, completed the PTQ. The study assessed tic severity using the Yale Global Tic Severity Scale (YGTSS) and PTQ. Additionally, obsessive-compulsive symptoms were measured using the Children Yale-Brown Obsessive Compulsive Scale (CY-BOCS), and other behavioral problems were evaluated using the Conners’ Parent Rating Scale (CPRS-48). Results The PTQ showed acceptable to good internal consistency (Cronbach’s alpha = 0.67 for motor, 0.77 for vocal, and 0.79 for total tic scores) and acceptable to good two-week test-retest reliability (intraclass correlations, ICC = 0.74 for motor, 0.81 for vocal, and 0.79 for total tic scores). It demonstrated good convergent validity with the YGTSS and effective discriminant validity from obsessive-compulsive and internalizing symptoms (i.e., anxiety and psychosomatic). Furthermore, our analysis revealed significant variability in item difficulty across the questionnaire, indicating differences in how various tics are perceived and reported by Chinese parents, which may influence the assessment’s accuracy and reliability. Discussion The findings indicate that the Chinese version of the PTQ is a reliable and valid tool for assessing tic severity in Chinese children with tic disorders, offering significant implications for clinical assessment in diverse cultural contexts. Additionally, our findings on item difficulty highlight the need for further cultural adaptations of the PTQ.